Chance constrained unit commitment considering comprehensive modelling of demand response resources. Issue 4 (6th February 2017) - Wang, Beibei; Yang, Xuechun; Short, Taylor; Yang, Shengchun
Abstract : This study proposes an incentive‐based demand response (IDR) unit commitment model considering different types of demand response (DR) resources. In the proposed IDR dispatch model, (i) different load characteristic patterns of DR users can be included, such as transfer‐type, shift‐type and clip‐type electricity users, and (ii) the uncertainty of DR participation behaviour is considered in the system reserve electricity using chance constrained programming. Simulation results for the Pennsylvania–New Jersey–Maryland (PJM) 5‐bus system and the Institute of Electrical and Electronics Engineers (IEEE) 118‐bus system indicate that the proposed model can achieve optimal DR scheduling while considering both economics and system reliability when high‐quality DR resources are limited. Moreover, the unique scheduling features of DR must be considered in addition to economics and flexibility when dispatching DR resources; the uncertainty of DR can affect the highest confidence level of system operation. In addition, some significant coefficients of the special dispatch constraints of IDR clearly influence the performance of IDR resources.